Analisis Tingkat Kepuasan Siswa terhadap Media Pembelajaran PowerPoint Interaktif Berbasis RPE pada Materi Listrik Searah - Zarkasyi, Achmad; Eddie, Sukiswo Supeni (UPEJ Unnes Physics Education Journal, 2021)
Creativity is one of the important competencies that must be possessed by humans in the 21st century. Creativity can be viewed from four approaches, namely personal, driver, process and product. According to Peter Nilsson product creativity can be assessed in terms of quality and product form. Based on Nilsson's Taxonomy design creativity the product form can be distinguished in five aspects namely imitation, variety, combination, transformation and original creation. This research focuses on product creativity of variation aspects conducted on physics education students class of 2017. Students are required to redesign pascal legal props and then assessed using expertly validated instruments. Data analysis techniques use a descriptive quantitative approach. The results of the data analysis showed the level of creativity of student product design variations fall into the high category with a score of 5.9 in the range of scales 1-7.